Optimal Embeddings of Calderón Spaces in Hölder-Zygmund Spaces - Bashir, Zia; Cobos, Fernando; Karadzhov, Georgi E. (MATHEMATICA SCANDINAVICA, 2014)
We prove optimal embeddings of Calderón spaces built-up over function spaces defined in $R^n$ with the Lebesgue measure into generalized Hölder-Zygmund spaces in the super-critical and critical cases.